(untitled) (Revista Contexto & Saúde, 2025)
Objective: To validate the content of a prior knowledge questionnaire, simulated scenario, and checklist used in realistic simulation for initial trauma care. Method: This methodological study was conducted in two stages: instrument development and content validation by expert judges. Data analysis was performed using the percentage of agreement among assessors regarding the retention or exclusion of instrument items. A minimum acceptance criterion of 80% agreement was established. Results: For the assessment of the prior knowledge questionnaire, simulated scenario, and checklist, an overall score of 8.8 was obtained, based on assessments from 12 and 8 judges, respectively. The instruments were assessed based on the percentage of agreement among judges. In the overall assessment, the instruments achieved an agreement index of 8.2, with a standard deviation of 0.7 and an average agreement score of 9.2 among the judges. Conclusion: The instruments demonstrated satisfactory validity evidence and may be used as educational tools for teaching this topic.